Association between Immunohistochemical profile and Clinicopathological appearance in Breast Cancer : A 7 year review from Mahdieh Radiotherapy Center, Hamadan, Iran - Akbari Hamed, Ehsan; Mohammadian, Kamal; Sedighi Pashaki, Abdolazim; Behnood, Sepideh; Abbasi, Mohammad; Babaei, Mohammad; Madah Safaee, Afsaneh; Torkaman, Tayebeh (Reports of Radiotherapy and Oncology, 2023)
Introduction: Invasive breast cancer is the most common carcinoma in women. Immunohistochemistry classification now plays a key role in prognostic identification and prediction of outcome in this disease. Based on recent gene expression studies, immunohistochemical subtypes are as follows: Luminal A (ER+ and /or PR+, HER2-), luminal B (ER+ and /or PR+, HER2+), HER2+/ ER-, PR-, and basal-like (ER-, PR-, HER2-). These molecular differences have been shown to correlate with clinical features, such as survival, and sensitivity to treatment. In this study we evaluated the association between different subtypes with histological type, grade, tumor stage, lymph node positive ratio, lymph node status, recurrence, and survival. Patients and Methods:We retrieved the clinical records of 580 patients with breast cancer who were treated at Mahdieh Institute of oncology in Hamadan, Iran between Oct 2004 and Oct 2011, and we evaluated clinicopathological data of these patients. Result: mean age of patients was 47.22 ± 11.1 years. Of 573 patients, 116 (20.2%) were ER /PR+, HER2+, 257 (44.9%) were ER /PR+, HER2- , 72 (12.6%) were ER /PR- , HER2+ , 124 (21.6%) were ER /PR- , HER2- and 4 were not undefined. The estimated median follow up period for all subjects was 4.9 years (range 3 months to 6.9 years). The overall survival for all patients was 88.21% and the disease free survival was 83.7%. The interesting result of this study was the lower incidence of positive axillary lymph nodes in triple negative subtypes. Five-year relative survival rates were higher for patients with ER/PR+ and negative lymph nodes (p< 0.05). Conclusion: This study highlighted the importance of immunohistochemical subtypes. As our patients were good representatives of breast cancer in western Iran and this study showed some differences with literature, further research should be directed at standardization of molecular and immunohistochemical methods in our country.